2007
DOI: 10.1108/02686900710718654
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of audit fees for French quoted firms

Abstract: This paper seeks to contribute to the international literature by researching the factors influencing audit fees in France. The French case is specific because the law requires a joint auditing process involving two separate auditors for firms that publish consolidated financial statements. Since 2003, the disclosure of audit fees has been compulsory in France, but numerous firms decided to voluntarily disclose their audit fees for the year 2002. We attempt here to elucidate the amount spent on audit fees in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
54
1
9

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(71 citation statements)
references
References 19 publications
7
54
1
9
Order By: Relevance
“…In contrast to the findings from Denmark (Thinggaard and Kiertzner, 2008), Gonthier-Besacier and Schatt (2007) show that balanced allocation between the auditors does not affect audit fees in France. They also show that companies audited by two Big 4 audit firms have a lower audit fee-size ratio compared to companies audited by other types of auditor pairs.…”
Section: Consequences Of the Joint Auditor Pair Choice And Of The Discontrasting
confidence: 49%
“…In contrast to the findings from Denmark (Thinggaard and Kiertzner, 2008), Gonthier-Besacier and Schatt (2007) show that balanced allocation between the auditors does not affect audit fees in France. They also show that companies audited by two Big 4 audit firms have a lower audit fee-size ratio compared to companies audited by other types of auditor pairs.…”
Section: Consequences Of the Joint Auditor Pair Choice And Of The Discontrasting
confidence: 49%
“…Size, reputation, experience, competition, industry specialization and whether it is from the Big Four are aspects of the audit company that influence audit fees as many prior studies suggested that audit fees increase with the Audit firm's Size (Francis, 1984;Palmrose, 1986), reputation (Larcker & Richardson, 2004, Gonthier & Schatt, 2007, experience, industry specialization (Pearson & Trompeter, 1994;Craswell et al, 1995;Cullinan, 1998) and whether it is one of the Big Four (Palmrose, 1986;Francis & Simon, 1987;Butterworth & Houghton, 1995). However, Audit fees decreases with the increase in competition, the greater the number of competitors the lower the audit fees are charged (e.g., Maher, Tiessen, Colson & Broman, 1992;Hay et al 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Reputation of the audit office is the perception that some audit firms can provide higher quality auditing than others, which is one of the most important factors affecting the audit service pricing (e.g., Larcker & Richardson, 2004;Gonthier & Schatt, 2007). Firms which have invested in reputation capital (e.g., employee training programs and advertising) suggests a much higher success rate of the audit firm (Che-Ahmad & Houghton, 1996), and therefore it may be able to obtain a return on its investment through placing higher audit fees for their services.…”
Section: Reputationmentioning
confidence: 99%
“…Also, auditor attributes are considered important drivers of audit fees such as reputation, experience, competition, industry (Palmrose, 1986;Pearson and Trompeter, 1994;hay et al, 2006 andGonthier andSchatt, 2007). Based on above, accounting researches have investigated various aspects of attributes in accounting profession, but all these studies have not examined the potential gender effects on audit fees.…”
Section: Literature Reviews and Research Questionmentioning
confidence: 99%